(untitled) (Journal of Computational Innovation and Analytics (JCIA), 2025)
The Philippine higher education sector underwent a significant curriculum transition with the implementation of the K–12 program, which reduced the engineering curriculum from five to four years. This study examines the impact of this change on the licensure examination performance of engineering graduates. A causal-comparative design was used, with propensity score matching (PSM) applied to control for confounding variables such as age, sex, academic performance, exam timing, and degree program. Both nearest-neighbor and full matching methods were tested, with full matching selected for its superior covariate balance and sample retention. Using the matched dataset, logistic regression modeling revealed that graduates under the new 4-year curriculum had significantly lower odds (OR = 0.94) of passing the board exam than those under the 5-year track. The marginal mean comparison showed a 6.06 percentage point decrease in passing probability for the new curriculum group (p < .001), with a Cohen’s d of –0.53, indicating a moderate negative effect. These findings suggest that transitioning to the restructured 4-year engineering curriculum has not yet translated into improved licensure performance. A closer review of curriculum content, implementation fidelity, and academic support programs is needed to address this gap and strengthen outcomes under the reformed education system.